Developing Vaza Clinic Business Strategy Using SWOT Analysis Approach - Chitra Octavia; Yolla Margaretha (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2024)
Skincare is a crucial element in the beauty industry. Beauty continues to evolve and has become essential, especially for women who want to look attractive, leading to the expanding global skincare industry, including in Indonesia. Herbal skincare with diverse service products and significant capital requires strategic planning. The Strategic Business Plan for Achieving Goals in Current Competition aims to develop a strategic business plan for Vaza Skincare Herbal Cosmetics Galactomyces. The research method involves descriptive analysis using a qualitative approach in processing primary and secondary data. Decision-making uses SWOT analysis, Internal Factor Analysis Strategy (IFAS), and External Factor Analysis Strategy (EFAS). The research results in a strategic business plan design for Vaza Skincare Herbal Cosmetics Galactomyces. Currently, Vaza Skincare Herbal Cosmetics Galactomyces only holds and maintains Cell V, with recommended strategies being market penetration and product development. Marketing strategies should be developed to increase purchases of Galactomyces herbal cosmetics and expand market share through mass communication such as informative advertising, persuasive advertising, reminder advertising, and reinforcement advertising. Another strategy is implementing digital communication through display, likes, comments, sharing, and satisfaction scores on Google Reviews to involve all managers and employees in the success of implementing the strategic plan for Vaza Skincare Herbal Cosmetics Galactomyces by ensuring strong commitment